Causes and contributing factors of maternal mortality in Bosaso District of Somalia. A retrospective study of 30 cases using a Verbal Autopsy approach - Jamila Ahmed Aden; Hinda Jama Ahmed; Per-Olof Östergren (Taylor & Francis Group, 2019)
Background: Somali women suffer from one of the highest maternal mortality rates in the world. Somalia characterises a specific low-income country situation with a mix of newly urbanized and nomadic culture combined with a frail health care infrastructure set in a post-conflict era. Very little is known about the effects that these contextual factors can have on maternal mortality. Objectives: To explore and describe causes and contributing factors concerning maternal deaths in the Bosaso District, Puntland State of Somalia. Methods: Data was collected using an adapted Verbal Autopsy tool. In 2017 30 cases of maternal deaths occurring in 2016 in the Bosaso District were reviewed. Information was assessed by three independent reviewers who classified the cause of death and the contributing factors. The Three Delay Model was employed to identify socio-cultural and economic and health system factors that may have contributed to these maternal deaths. Results: Direct obstetric deaths accounted for 28 cases. Among these, haemorrhage was the leading cause, followed by eclampsia, sepsis and obstructed labour. Two cases were indirect obstetric deaths, caused by anaemia. All three types of delay were frequent among the studied cases. Delay in deciding to seek care was found in 25 cases, delay in reaching care in 22 cases and delay in receiving health care in 24 cases. Lack of knowledge, money, transportation, poor access and availability of adequate services, as well as substandard management by health care providers, were all underlying the delays. Conclusion: A comprehensive intervention programme is needed in order to decrease maternal mortality among Somali women. Such a programme must include health education, improved referral systems and strategic upgrading of care services.